2021
DOI: 10.1029/2020jb020177
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Transition Zone Receiver Functions for Bermuda: Automation, Quality Control, and Interpretation

Abstract: Intraplate, or hot-spot, volcanism is typically interpreted as the result of plate motion over a spatially localized region of long-lived deep-mantle upwelling (Morgan, 1971). Arguably the most famous example of this process is the Hawaiian-Emperor Seamount Chain (e.g., Steinberger et al., 2004). Whether Bermuda belongs in this category of an intraplate volcano originating from a deep-mantle plume source remains uncertain. The island of Bermuda, situated atop a roughly 10 6 km 2 bathymetric swell in the Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…In principle, an ideal RF represents the impulse response due to structure directly beneath a seismic station, because signature of the source and source‐side structure is removed through deconvolution (e.g., Ammon, 1991). Thus, unlike many other seismic methodologies that require a network of seismometers, RF analysis can extract useful structural constraints even when a single three component seismic station is available (e.g., Burky et al., 2021; Kim and Lekić, 2019; Panning et al., 2017). Extraction of rich information contained in RFs at a single station can be achieved by incorporating many independent measurements from both Ps ‐RFs and the corresponding free‐surface reverberations contained in the same record.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, an ideal RF represents the impulse response due to structure directly beneath a seismic station, because signature of the source and source‐side structure is removed through deconvolution (e.g., Ammon, 1991). Thus, unlike many other seismic methodologies that require a network of seismometers, RF analysis can extract useful structural constraints even when a single three component seismic station is available (e.g., Burky et al., 2021; Kim and Lekić, 2019; Panning et al., 2017). Extraction of rich information contained in RFs at a single station can be achieved by incorporating many independent measurements from both Ps ‐RFs and the corresponding free‐surface reverberations contained in the same record.…”
Section: Introductionmentioning
confidence: 99%
“…The variable mantle transition zone thickness is interpreted, within the context of mineralogical composition 13,14 , as sensitive to temperature differences from the ambient mantle 8 . Using average mantle properties and published estimates for the relevant Clapeyron slopes 15 , a 100 K temperature increase implies a ~15 km thinning of the mantle transition zone (hereafter: MTZ).…”
mentioning
confidence: 99%
“…(IV) Can mantle plumes that rise from broad upwelling regions anchored at the CMB, as is apparently the case beneath Marquesas (Lei et al 2020;French & Romanowicz 2015), stall in the lower mantle? (V) Do some hotspots originate from within or just below the mantle transition zone (Benoit et al 2013;Burky et al 2021), as suggested by the structure beneath Tahiti and Louisville, or does that reflect a lack of resolution? Does the Large Low Shear-Velocity Province at the CMB beneath Samoa and Tahiti give rise to multiple plume conduits (Garnero et al 2016), as beneath La Réunion (Wamba et al 2023)?…”
mentioning
confidence: 99%